Respuesta :

Answer:

[tex]x=-3(+/-)3\sqrt{2}[/tex]

Step-by-step explanation:

we know that

The formula to solve a quadratic equation of the form

[tex]ax^{2} +bx+c=0[/tex]

is equal to

[tex]x=\frac{-b(+/-)\sqrt{b^{2}-4ac}} {2a}[/tex]

in this problem we have

[tex]x^{2} +6x-9=0[/tex]  

so

[tex]a=1\\b=6\\c=-9[/tex]

substitute in the formula

[tex]x=\frac{-6(+/-)\sqrt{6^{2}-4(1)(-9)}} {2(1)}[/tex]

[tex]x=\frac{-6(+/-)\sqrt{72}} {2}[/tex]

[tex]x=\frac{-6(+/-)6\sqrt{2}} {2}[/tex]

[tex]x=-3(+/-)3\sqrt{2}[/tex]